2008
DOI: 10.1152/japplphysiol.01084.2007
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of hand cooling at reducing exercise-induced hyperthermia and improving distance-race performance in wheelchair and able-bodied athletes

Abstract: The purpose of this study was to examine the effectiveness of reducing core temperature in postexercise hyperthermic subjects and to assess if hand cooling (HC) improves subsequent timed distance performance. Following a detailed measurement check on the use of insulated auditory canal temperature (T(ac)), eight wheelchair (WA) athletes and seven male able-bodied (AB) athletes performed two testing sessions, comprising a 60-min exercise protocol and 10-min recovery period, followed by a performance trial (1 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 24 publications
1
56
2
3
Order By: Relevance
“…Foot cooling garments, hand cooling garments, head and neck cooling garments, misting devices, and a cooling vest have been tested in SCI populations. [18][19][20][21][22] This study sought to test the efficacy of the cooling device in a sport-specific environment. The cooling vest interferes minimally with wheelchair propulsion during sporting activities and was thus chosen for this study.…”
mentioning
confidence: 99%
“…Foot cooling garments, hand cooling garments, head and neck cooling garments, misting devices, and a cooling vest have been tested in SCI populations. [18][19][20][21][22] This study sought to test the efficacy of the cooling device in a sport-specific environment. The cooling vest interferes minimally with wheelchair propulsion during sporting activities and was thus chosen for this study.…”
mentioning
confidence: 99%
“…However, during periods of extreme exercise or other types of physical exertion, body temperatures may be mildly elevated (Goosey-Tolfrey et al, 2008;Ö zgü nen et al, 2010). In a study by Ö zgü nen and colleagues (2010), body temperature was reported to rise to 39°C in football players during periods of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has also supported the use of hand cooling in reducing physiological heat strain 44 and improving performance. 43,45 While there is evidence showing that hand cooling attenuates the rise of body temperature during exercise and improves performance, its effectiveness in preexercise and postexercise body cooling remains questionable due to the low cooling rate of 0.05°C/min. 43,46,47 …”
Section: Hand Coolingmentioning
confidence: 99%